THE LECTURERS' PERCEPTION ON ESP COURSE DESIGN AT NON-ENGLISH DEPARTMENT IN INDONESIA UNIVERSITY OF EDUCATION - Annisa Rahmah Jalilah, - (2010)
THE LECTURERS' PERCEPTION ON ESP COURSE DESIGN AT NON-ENGLISH DEPARTMENT IN INDONESIA UNIVERSITY OF EDUCATION This study tries to investigate the lecturers' perception on formulating the goals in teaching English, on developing and organizing the materials, on implementing the methodology in teaching English, and on developing the evaluation in teaching English for students of Tourism Marketing Management Program (Faculty of Social Science) at non-English Department of University of Education (UPI) Bandung. The writer uses a descriptive method which is largely qualitative. A descriptive analysis is conducted to answer the following research problems: (a) What are the lecturers' perceptions on formulating the goals for students of Tourism Marketing Management Program? ; (b) What are the lecturers' perceptions on developing materials for students of Tourism Marketing Management Program? ; (c) What are the lecturers' perceptions on implementing methodology in teaching English for students of Tourism Marketing Management Program?; And (d) what are the lecturers' perceptions on developing evaluation for students of Tourism Marketing Management Program? The subjects of the research are the English lecturers of Tourism Marketing Management Program of Indonesia University of Education. The data were obtained by utilizing some instruments including questionnaire, interview, and documentary study. The results show that the goals of teaching English for tourism and marketing students program are to enable the students to use English in their factual life in the future and to get a good score in TOEIC test. These goals are determined due to the fact that the students need English to communicate and promote tourism field to the tourists, especially from another country. Besides, they need to get a good TOEIC score for job search in their future after they graduate. To achieve the goals, the lecturers provide the learners with authentic and modified materials. The materials include a number of reading texts adopted from the textbooks of learners' discipline, magazines, newspaper, internet, and a series of task related to the texts. Therefore, the teaching strategies applied by the lecturers are closely related to text discussion, lecturing, and presentation. Then, the students are asked to work out the exercises concerning the content of the text. Furthermore, the lecturers conduct both learner assessment and course evaluation. They are used to measure whether the learners have achieved the learning objectives (leaner assessment) and whether the course is doing what it was designed to do (course evaluation). Key words: Perception Course Design English for Specific Purposes English for Tourism